Assessment the reliability of ultrasonography in the imaging of the plantar fascia: a comparative study - Wu, Jing; Zhang, Yuan-zhi; Gao, Yang; Luo, Tian-you (BMC medical imaging, 2019)
Imaging methods for the plantar fascia have included radiography, ultrasound and magnetic resonance imaging (MRI), all of which have provided valuable information. This study assessed the reliability of ultrasonography examinations of the plantar fascia using a comparative study. Fifty healthy adult volunteers (25 males and 25 females, mean age 31.6 ± 3.5 years) were included in this study. Images of the plantar fascia from 100 ft were acquired with ultrasonography, CT and MRI. Ultrasound was used to measure the thickness of the plantar fascia. Imaging data from CT and MRI in a DICOM format were transformed into the Materialise Mimics Innovation Suite 16.0 software for digital analysis. SPSS software (SPSS, USA) was used for statistical analysis. The reliability was established by a t-test. Moreover, 42 patients with unilateral plantar fasciitis were examined by ultrasonography. There were no significant differences between the three imaging modalities for patients of the same sex (P > 0.05). There were no statistically significant differences between the left and right sides for patients of the same sex (P > 0.05), but the difference between males and females was statistically significant (P < 0.01). There were no significant differences between US, CT and MRI in the normal group, but there were significant differences in the plantar fasciitis group evaluated with ultrasound. The plantar fascii of normal male subjects are significantly thicker than those of the normal female. Ultrasonography can be a relatively simple and reliable method for the measurement of plantar fascia thickness.